2019
DOI: 10.1136/bmjopen-2019-031546
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in reporting workplace violence: a qualitative analysis of administrative records of violent episodes experienced by healthcare workers in a large public Italian hospital

Abstract: ObjectivesThis study aims to analyse, from a descriptive and qualitative point of view, the episodes of violence reported by healthcare workers (HCWs) in a large public Italian hospital. Qualitative analysis permits us to collect the victims’ words used to describe the event and the ways in which they dealt with it. A comparison between genders was performed to better understand what type of different strategies could be used to improve the prevention of workplace violence for HCWs.Design and settingThe retros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
22
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 40 publications
5
22
0
1
Order By: Relevance
“…This difference, however, could be explained by the fact that males tend to report exposure to violence more easily than females. (21) It was found that younger physicians aged below 30 years were at a significantly higher risk for WPV compared to older ages. Also, those with less than 5 years of experience were at significantly higher risk of exposure to violence than those with more experience.…”
Section: Discussionmentioning
confidence: 98%
“…This difference, however, could be explained by the fact that males tend to report exposure to violence more easily than females. (21) It was found that younger physicians aged below 30 years were at a significantly higher risk for WPV compared to older ages. Also, those with less than 5 years of experience were at significantly higher risk of exposure to violence than those with more experience.…”
Section: Discussionmentioning
confidence: 98%
“…Workplace violence in healthcare workers has been extensively studied in the occupational health literature [ 85 , 86 , 87 ]. Healthcare workers in conflict settings reported both physical and non-physical workplace violence.…”
Section: Discussionmentioning
confidence: 99%
“…While studies in this review found that physical violence was more common among male HCWs practicing in conflict zones [ 62 , 63 ], another study found no sex/gender differences in exposure to violence [ 61 ]. However, findings in the occupational health literature on healthcare workers in various workplace settings showed that males reported higher exposures to physical violence and abuse [ 86 , 87 ] and females reported higher exposures to non-physical violence, such as verbal abuse, threats, and sexual harassment [ 14 , 87 ]. A study on close-to-community health service providers revealed that insecurity was a prevalent and recurring theme for female workers, due to high risks of gender-based violence and sexual harassment in certain communities, which become more prominent in conflict-ridden areas [ 88 ].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of physical WPV ranged from 4.9%–83.3% and verbal WPV from 66.2%–95.1% in the prior year among nurses (Jakobsson et al., 2020; Shi et al., 2020). Regards to association between gender and physical and verbal WPV, prior findings found are contradictory (Acquadro Maran et al., 2019; Li et al., 2020).…”
Section: Workplace Violence (Wpv) In Healthcare Systemsmentioning
confidence: 92%